Stochastic analysis of moderately thick plates using the generalized polynomial chaos and element free Galerkin method. (June 2017) - Bahmyari, Ehsan; Khedmati, Mohammad Reza; Soares, C. Guedes
Abstract: In this paper, the element free Galerkin method is combined with the generalized polynomial chaos to quantify the uncertainties in the bending analysis of shear deformable plates with elastically restrained edges resting on a Pasternak elastic foundation with random system properties. The plate modules of elasticity, stiffnesses of the elastically restrained edges and the foundation stiffnesses are considered as random processes and are represented by using the Karhunen–Loève expansion. It is shown that the results obtained by the presented method are in a very good agreement with the results of Monte Carlo simulations in spite of using low order polynomials in the generalized polynomial chaos expansion. Also the applicability and versatility of the presented method are demonstrated by solving numerical examples for various values of coefficient of variations, aspect ratio, thickness and several combinations of boundary conditions, different types of lateral loading and various values of stiffnesses of restrained edges and elastic foundation.